Push and Pull Factors and their effects on International Tourists’ Revisit Intention to Nepal - Baniya, Rojan; Ghimire, Suman; Phuyal, Sandip (The Gaze: Journal of Tourism and Hospitality, 2017)
International tourists are of great prominence to Nepali economy, consequently their motivation to visit Nepal should guide the success of Nepal as tourist destination. The primary objective of this study is to use commonly recognized ‘integrative models of push and pull motives’ to travel motivations of international tourists to Nepal. Based on previous studies, inspecting the direct effect of push and pull motives on international tourists to Nepal, this study proposes that except for ‘enhancing social’, all the other variables (pull factors – nature, culture and heritage sites, adventure, friendly people climate; push factors – relaxation and recreation, enhance relationship, fulfilling practice, escape from daily routine) exhibited encouragingly positive correlation with re-visit intentions among international tourist to Nepal. Additionally, the overall push factors and pull factors together predicted the revisit intention of international tourists to Nepal, however push factor was insignificant. Thus, convincingly, we could say that international tourists are motivated to visit Nepal by its pull factors i.e. destination attributes. The study’s findings reveal Nepal’s international tourists’ impetuses, and provide practitioners and policymakers with a foundation to develop an effective strategy to improve the international tourist based tourism in Nepal. The GAZE Journal of Tourism and Hospitality, Vol. 8, 2017, page: 20-39